On the applicability of multi-surface, two-surface and non-linear kinematic hardening models in multiaxial fatigue - M.A Meggiolaro; J.T.P. Castro; H. Wu (Fracture and Structural Integrity)
In this work, a comparison between NLK and Mróz-Garud’s multi-surface formulations is presented. A unified common notation is introduced to describe the involved equations, showing that the Mróz-Garud model can be regarded as a particular case of the NLK formulation. It is also shown that the classic two-surface model, which is an unconventional simplified plasticity model based on the translation of only two surfaces, can also be represented using this formulation. Such common notation allows a direct quantitative comparison among multi-surface, two-surface, and NLK hardening models.